2019
DOI: 10.1186/s12889-019-7223-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the implementation of a pilot smoking cessation intervention among migrant workers in Chinese factories: a qualitative study

Abstract: Background Tobacco control intervention with Chinese internal migrants, especially those working in factories has rarely been investigated. This study aims to identify aids and barriers to implementing a comprehensive pilot intervention aimed at reducing smoking among migrant workers working in factories in China. Method Twenty in-depth interviews were conducted 3 months into the intervention, with managers, migrant workers and team leaders in two factories, where the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Consistent with another study [20], our study suggests social factors are deeply embedded in the challenges of lifestyles modifications such as smoking and drinking. Future intervention should strengthen the quality of health education, for instance, to include social elements and relationships in the delivery of education.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with another study [20], our study suggests social factors are deeply embedded in the challenges of lifestyles modifications such as smoking and drinking. Future intervention should strengthen the quality of health education, for instance, to include social elements and relationships in the delivery of education.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies on migrant TB delay [26][27][28][29], our study showed that migrant TB patients with DM tended to have longer patient delays and a higher proportion of patients with patient delay> 14 days (although without statistical significance). This may be due to poor health awareness and health behavior among TB-affected migrants because of their poor socioeconomic characteristics, such as job instability, low income, poor living and working conditions [30][31][32][33][34]. In addition, our univariate analysis suggests that migrant TB patients with DM tended to have longer health system delays, total delay and a higher risk of health system delay> 14 days.…”
Section: Comparison With Literaturementioning
confidence: 79%
“…Based on the results of a literature study from the PubMed database, a comparison of the factors that support the success of smoking cessation, found 11 articles, several articles that show the success of quitting smoking, namely: a. Zou, Guanyang., (2019), titled "Factors influencing the implementation of a pilot smoking intervention for migrant workers in Chinese factories: a qualitative study" describes that supports the success of quitting smoking by providing group counseling and knowledge to stop smoking [4]. b.…”
Section: Supporting Factors For the Success Of Quitting Smokingmentioning
confidence: 99%